Data-Driven Decision Support in Obesity Management Commission : enabling more equitable and personalized obesity care - Franks, Paul W.; Suliman, Sara G.I.; Timpson, Nicholas J.; Langenberg, Claudia; le Roux, Carel W. (Nature Medicine, 2026)
Announced in this Comment and in collaboration with Nature Medicine is the convening of the Data-Driven Decision Support in Obesity Management Commission, to promote adequate scientific evidence to support obesity management across global populations.